The future of the euro (New York, 2015)
"The Future of the Euro is an attempt by political economists to analyze the fundamental causes of the euro crisis, determine how it can be fixed, and consider what likely futures lie ahead for the currency. The book makes three interrelated arguments that emphasize the primacy of political over economic factors. First, the 'euro problem' is discussed as the result of the single currency's fundamental lack of institutional embeddedness, insofar as its original design omitted three 'forgotten unions' alongside of monetary union: a financial and banking union, mutually supporting institutions of fiscal union and economic government, and a political union holding similar legitimacy to the nation-state. Second, the 'euro experience' shows how the euro's unfinished design led to economic divergence - quietly altering the existing distribution of economic and political power within Europe prior to the crisis - which in turn determined the EU's crisis response. The book highlights how the euro's four most important members - Germany, France, Italy and Spain - each changed once they adopted the euro, why the crisis affected them so differently, and how each has since struggled to live with the commitments the euro necessitates. Third, the book examines three possible 'euro futures' through the lens of the politics of its reluctant leader Germany; through the lens of the EU's capacity to 'move forward' through crises; and through the geopolitical lens of the international monetary system. The book concludes that any successful long-term solution to the euro's predicament needs to start with the political foundations of markets."